2023
DOI: 10.3389/fnins.2023.1161904
|View full text |Cite
|
Sign up to set email alerts
|

Persistent olfactory dysfunction associated with poor sleep quality and anxiety in patients with long COVID

Alna Carolina Mendes Paranhos,
Apio Ricardo Nazareth Dias,
Thalita da Rocha Bastos
et al.

Abstract: IntroductionPoor sleep quality have been widely reported in patients with long COVID. Determining the characteristics, type, severity, and relationship of long COVID with other neurological symptoms is essential for the prognosis and management of poor sleep quality.MethodsThis cross-sectional study was conducted at a public university in the eastern Amazon region of Brazil between November 2020 and October 2022. The study involved 288 patients with long COVID with self-report neurological symptoms. One hundre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Similar results were described by Bolattürk and Soylu (2023) in a sample of forty PCC participants, where the PSQI score did not correlate with the MoCA or MMSE score; instead, the MoCA score correlated with the Hamilton Depression Scale score. More examples of the relationship between sleep quality and other variables, such as anxiety, can be found in this study, which also analysed olfactory dysfunction in patients with long COVID ( Paranhos et al, 2023 ). The authors did not find an association between sleep quality and cognition (measured with the MoCA).…”
Section: Discussionmentioning
confidence: 94%
“…Similar results were described by Bolattürk and Soylu (2023) in a sample of forty PCC participants, where the PSQI score did not correlate with the MoCA or MMSE score; instead, the MoCA score correlated with the Hamilton Depression Scale score. More examples of the relationship between sleep quality and other variables, such as anxiety, can be found in this study, which also analysed olfactory dysfunction in patients with long COVID ( Paranhos et al, 2023 ). The authors did not find an association between sleep quality and cognition (measured with the MoCA).…”
Section: Discussionmentioning
confidence: 94%
“…A recent cross-sectional study published by our group of 288 patients with long COVID showed that the presence of anxiety is a risk factor for poor sleep quality, and that patients with sleep disorders more frequently report symptoms of anxiety ( Paranhos et al, 2023 ). Anxiety and insomnia have common pathophysiological mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Different odours have been demonstrated to modulate mood, and feelings of stress and anxiety ( Lehrner et al, 2000 ; Fukada et al, 2011 ; Kaimal et al, 2020 ). During and following the years of COVID-19 infection the impact to olfaction due to infection complications became a significant metric for long-COVID effects ( Kapoor et al, 2021 ; Tan et al, 2022 ; Paranhos et al, 2023 ). Further research could advise applications of olfaction interventions in health and wellbeing.…”
Section: Introductionmentioning
confidence: 99%